Perancangan Mesin Pencacah Sampah Plastik Kapasitas 85 Kg - Tjiroso, Bambang; Latif, Lita Asyriati (Patria Artha Technological Journal, 2021)
Pollution of plastic waste to the environment is a big obstacle because plastic waste is difficult to recycle directly. Waste management should implement processes, such as reduce, reuse, recycle and replace potentially waste items into Recycle (Replace) materials. Recycling plastic waste has the potential to change what was previously waste that has no economic value into an item that has economic value and at the same time reduces environmental pollution problems. The purpose of this study was to design a plastic waste chopper with a capacity of 85Kg. The method used in this research is the method of design and calculation. The results of the design of a plastic chopping machine with a capacity of 85Kg, the dimensions of the shaft length are 50cm, the shaft diameter is 8cm and the cutting blade holder is connected to the shaft. The blade is designed so that it can be adjusted forward and backward according to the thickness of the plastic to be chopped. There are 6 dynamic blades and 2 static blades. The cutting angle of the blade is 45°. The hooper design has dimensions of 40cm long, 40cm wide and 60cm high with a plate thickness of 0.8mm. The frame of the garbage chopper has dimensions of 40cm long, 40cm wide and 70cm high. The result of calculating the engine capacity on a plastic chopper with a capacity of 85kg hour is 1400g minute.